1992
DOI: 10.1039/an9921701243
|View full text |Cite
|
Sign up to set email alerts
|

Novel conducting polymers incorporating covalently bound metal–tetraazamacrocycle complexes

Abstract: The syntheses of a tetraazamacrocycle functionalized at nitrogen with a pendant 3-thiophene, 1 -[2-(3thienyl)ethyl]-l,4,8,1 I-tetraazacyclotetradecane (cyclamN-CH2CH2-thiophene), and its complexes with Nil1 and Cull, are described. Electro-oxidation of the pure Nil1 complex in acetonitrile electrolytes afforded only soluble oligomers. Novel conducting polymer-modified electrodes were fabricated, however, by electrocopolymerization of the Nil' complex with 3-methylthiophene. These are unusual in that both the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…[72] This covalent link approach has been most extensively applied to PPy, [73±84] and also to PT. [85,86] It has also been used for PAni [87] but in this case a general application of the method is much restricted due to the high reactivity of the amino group.…”
Section: Oi Materialsmentioning
confidence: 99%
“…[72] This covalent link approach has been most extensively applied to PPy, [73±84] and also to PT. [85,86] It has also been used for PAni [87] but in this case a general application of the method is much restricted due to the high reactivity of the amino group.…”
Section: Oi Materialsmentioning
confidence: 99%
“…Sable et al reported the formation of a poorly conducting film, [16] while Higgins found under similar conditions that soluble oligomers were formed. [17,18] Both groups have prepared electrochromic copolymers from mixtures of 4 and 3-methylthiophene. The films are red-orange when neutral, green when only the thiophene backbone is oxidized, and blue upon oxidation of both the Ni centers and the backbone.…”
Section: Polymers With Tethered Cyclam and Porphyrin Complexesmentioning
confidence: 99%
“…The films are red-orange when neutral, green when only the thiophene backbone is oxidized, and blue upon oxidation of both the Ni centers and the backbone. [17] A thiophene derivative with a porphyrin attached (5) has been electropolymerized. [19] The resulting films were reacted with Ni 2+ after deposition, and a Ni 2+/3+ redox wave was observed at 0.45 V vs. saturated calomel electrode (SCE) in the modified films, even though the backbone is insulating at this potential.…”
Section: Polymers With Tethered Cyclam and Porphyrin Complexesmentioning
confidence: 99%
“…Hybrid materials, combining conductivity of conducting polymers and redox properties of transition metal ions, represent an appealing alternative to the redox polymers, taking advantage of synergic electronic interactions. 2 Conducting polymers bearing different residues capable of coordinating different metal ions, such as cyclams, [3][4][5] porphyrins, [6][7][8] bipyridines, 9 and Schiff-bases, 10 are reported in several studies. However, the long-chain 'spacer' used to link the polymer and binding residue leads to a degree of separation between the polymer p-electron system and the metal.…”
Section: Introductionmentioning
confidence: 99%